High‐content screening of Alzheimer's disease genetic risk factors based on synaptic density analysis. (31st December 2021) - Coulon, Audrey; Mendes, Tiago; Kilinc, Devrim; Dumont, Julie; Chapuis, Julien; Lambert, Jean‐Charles
Abstract: Background: Synaptic loss is one of the earliest pathological hallmarks and the strongest marker of cognitive decline in Alzheimer's disease (AD). A strong genetic predisposition is linked to AD, and genome‐wide association studies have pointed out hundreds of genes associated with the risk of developing the disease. With this background, our objective is to develop a cell‐based screen to assess the impact of each genetic risk factor on synaptic density. Method: We screened a lentiviral shRNA library targeting 200 AD genetic risk factors using primary rat hippocampal neurons in 384‐wells plates. Immunofluorescence was performed to reveal pre‐ and post‐synaptic compartments and the neuronal network. Synaptic connectivity was then assessed through high content analysis by assigning each post‐synaptic structure to the nearest pre‐synaptic structure using Columbus and Matlab software. Result: We identified several AD risk genes which positively or negatively impacted synaptic density in our model. Conclusion: We have developed a high‐content screening approach which allows us to define the genetic risk factors that are involved in the pathophysiological synaptic dysregulation observed in the early stages of AD.